2021
DOI: 10.1136/bmjopen-2020-046476
|View full text |Cite
|
Sign up to set email alerts
|

Safety of topical corticosteroids in atopic eczema: an umbrella review

Abstract: ObjectiveAn umbrella review summarising all safety data from systematic reviews of topical corticosteroids (TCS) in adults and children with atopic eczema.MethodsEmbase, MEDLINE, PubMed, Cochrane Database of Systematic Reviews and the Centre of Evidence Based Dermatology map of eczema systematic reviews were searched until 7 November 2018 and Epistemonikos until 2 March 2021. Reviews were included if they assessed the safety of TCS in atopic eczema and searched >1 database using a reproducible search strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 86 publications
1
30
0
3
Order By: Relevance
“…Indeed, in paediatric patients, AD management mostly relies on emollients and topical corticosteroids (TCs). TCs should be used with caution in children because their body surface area to weight ratio is higher than in adults; as a result, they have a high degree of drug absorption [ 4 ]. For this reason, the potential for both cutaneous and systemic side effects, including possible hypothalamic-pituitary-adrenal axis suppression, should be considered [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in paediatric patients, AD management mostly relies on emollients and topical corticosteroids (TCs). TCs should be used with caution in children because their body surface area to weight ratio is higher than in adults; as a result, they have a high degree of drug absorption [ 4 ]. For this reason, the potential for both cutaneous and systemic side effects, including possible hypothalamic-pituitary-adrenal axis suppression, should be considered [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mild-and moderate-potency TCS have been shown to be safe to use in young children if they are used in the short term; however, data on long-term safety are limited. In their recent meta-analysis, Axon et al 29 found no evidence of safety issues in children when TCS were used intermittently. The risk for systemic absorption, immunosuppression and adrenal insufficiency seems to be very low.…”
Section: Discussionmentioning
confidence: 99%
“…24 Reducing topical corticosteroid use might be desirable in terms of simplifying treatment burden and minimising the risk of adverse effects, but should not distract from the appropriate use of topical corticosteroids to treat inflamed skin. 25 The findings from a nested qualitative study emphasised how the acceptability of the same product varies between users. 26 These findings are consistent with previous qualitative research, which identifies trade-offs between effectiveness and acceptability when choosing an emollient.…”
Section: Discussionmentioning
confidence: 99%